DEVELOPING COURSES IN THE BEHAVIOURAL AND SOCIAL SCIENCES FOR MEDICAL STUDENTS: NEW PROSPECTS FOR AN OLD PROBLEM - Peter J.Blizard, Peter J.Blizard (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1976)
This paper described methods which can be used to construct "behavioural objectives" at the level of a Department of Social and Behavioural Sciences within a Faculty of Medicine, and also in the choice of Specific curricular content. An attempt is then made to(i) Identify the basic skills that studies in the social and behavioural science might seek to develop in medical students ;(ii) Develop a set of Departmental Objectives which arise out of these basic skills, so that courses in these areas are as realistic and as practical as possible ;(iii) Extend this approach and show how it might be used as a method for developing a specific and measurable curriculum in the social and behavioural sciences ;. (iv), Identify some basic practical problems arising from a decision, by a Faculty of Medicine, to incorporate aspects of the social and behavioural sciences into the curriculum.For illustrative purposes each of the above tasks has been applied to the Indonesian context. It may thus be expected to have direct practical application to nther, similar developing countries ; but, of course, the approach to curriculum design will have more widespread application.